Rotavirus Infection in Children is an Unsolved Problem. Review of Guidelines for Vaccinal Prevention - Alexandr A. Baranov; Leyla S. Namazova-Baranova; Vladimir K. Tatochenko; Elena A. Vishneva; Marina V. Fedoseenko; Lilia R. Selimzianova; Yuriy V. Lobzin; Susanna M. Kharit; Mariya K. Bekhtereva; Nikolay I. Briko; Alla Ya. Mindlina; Vitaliy V. Kudryavtsev; et al. (Педиатрическая фармакология)
These clinical guidelines were developed by the professional association of pediatric specialists «Union of Pediatricians of Russia» and approved by the Association’s Executive Committee at the Congress of Pediatricians of Russia «Actual Problems of Pediatrics». Clinical guidelines are devoted to the problem of rotavirus infection, the relevance of which is determined by the high prevalence level and significant contribution of infectious diarrhea to the mortality pattern of children in the first 5 years of life. We present epidemiological data and detailed information on the infectious agent and pathogenesis of rotavirus infection progression. A detailed picture of clinical manifestations as well as extraintestinal complications is presented. The approach to specific prophylaxis has been reasoned. Practical recommendations for immunization as well as various regimens for administering the vaccine, depending on the age and condition of the patient, are given.